Pneumonia in the developing world: Characteristic features and approach to management. Issue 7 (6th July 2017) - Aston, Stephen J.
ABSTRACT: Community‐acquired pneumonia (CAP) is a common cause of morbidity and mortality in adults worldwide, but its epidemiology varies markedly by region. Whilst in high‐income countries, the predominant burden of CAP is in the elderly and those with chronic cardiovascular and pulmonary co‐morbidity, CAP patients in low‐income settings are often of working age and, in sub‐Saharan Africa, frequently HIV‐positive. Although region‐specific aetiological data are limited, they are sufficient to highlight major trends: in high‐burden settings, tuberculosis (TB) is a common cause of acute CAP; Gram‐negative pathogens such as Klebsiella pneumoniae are regionally important; and HIV‐associated opportunistic infections are common but difficult to diagnose. These differences in epidemiology and aetiological profile suggest that modified approaches to diagnosis, severity assessment and empirical antimicrobial therapy of CAP are necessary, but tailored individualized management approaches are constrained by limitations in the availability of radiological and laboratory diagnostic services, as well as medical expertise. The widespread introduction of the Xpert MTB/RIF platform represents a major advance for TB diagnosis, but innovations in rapid diagnostics for other opportunistic pathogens are urgently needed. Severity assessment tools (e.g. CURB65) that are used to guide early management decisions in CAP have not been widely validated in low‐income settings and locally adapted tools are required. The optimal approach to initial antimicrobial therapy choices such as the need to provide early empirical cover for atypical bacteria and TB remain poorly defined. Improvements in supportive care such as correcting hypoxaemia and intravenous fluid management represent opportunities for substantial reductions in mortality.